Alternative hypotheses of cross-country convergence: A non-parametric analysis of manufacturing sectors - Silvia Dal Bianco (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
This paper examines labour productivity convergence tendencies, among 28 developed and developing countries, in manufacturing sectors, identified by production's technological content. A unified distribution dynamics framework is employed to test absolute and conditional convergence hypotheses, together with club convergence inner drivers, namely capital and technological initial conditions. The results provided are consistent with the hypothesis of club convergence in Resource Based, Low and Medium Technology sectors and with the hypothesis of absolute convergence in High Technology and Manufacturing as a whole. In particular, club convergence seems to be driven by technological initial conditions in Resource Based and Low Technology sectors, while both capital and technology are determinant for Medium Technology overall convergence. This evidence shows that to catch-up with their richer counterparts, developing countries should enter R&D intense industries and target their industrial policy towards the development of dynamic advantages, such as knowledge and skills, rather than relying only on large production capacity, cheap labour and abundant natural resources.
Keywords: C14; O33; O47; 330; labour productivity convergence; distribution dynamics; stochastic kernel; ergodicdistribution; technological transfer; manufacturing sectors